PLANEJAMENTO FORRAGEIRO APLICADO EM UMA PROPRIEDADE RURAL - Vargas, Fabiane Da Motta; Santos, Angelica De Assis; Silva, Rodrigo Da; Argenta, Cláudia Vanessa; Favaretto, Marina; Pereira, Emerson André (Salão do Conhecimento, 2019)
Pesquisa institucional desenvolvida no Departamento de Estudos Agrários-DEAg/UNIJUÍ.